2022
DOI: 10.3390/diagnostics12040790
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Progesterone Receptor Immunohistochemical Expression to Predict Lymph Node Metastasis in Endometrial Cancer

Abstract: Background: Previous studies have shown that loss of progesterone receptor (PR) in endometrial cancer (EC) is associated with poor outcomes. Evaluating lymph node metastasis (LNM) is essential, especially before surgical staging. The aim of this study was to investigate the role of PR expression and other clinicopathological parameters in LNM and to develop a prediction model. Methods: We retrospectively evaluated endometrioid-type EC patients treated with staging surgery between January 2015 and March 2020. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In our previous study, we found that lower levels of PR expression, measured semiquantitatively, were associated with LNM. When incorporating PR expression into a prediction model with 2 other parameters, tumor grade and CA 125 levels, we demonstrated good prediction performance (9). The major concern was that the tissues we obtained for analysis were from hysterectomy specimens but not from pretreatment endometrial curettage.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our previous study, we found that lower levels of PR expression, measured semiquantitatively, were associated with LNM. When incorporating PR expression into a prediction model with 2 other parameters, tumor grade and CA 125 levels, we demonstrated good prediction performance (9). The major concern was that the tissues we obtained for analysis were from hysterectomy specimens but not from pretreatment endometrial curettage.…”
Section: Discussionmentioning
confidence: 91%
“…Given that endometrioid ECs are typically hormone-dependent, and previous studies have shown that the loss of estrogen receptor/progesterone receptor (ER/PR) is associated with tumor progression and poor survival outcomes 8 , it is reasonable to investigate whether hormone receptor status could be a predictive parameter. We previously found that PR measurement in a semiquantitative manner, in conjunction with tumor grade and CA 125, could help estimate the probability of LNM 9 . However, the relationship between ER status and LNM has not yet been investigated, and the predictive value of ER status remains unclear.…”
mentioning
confidence: 99%
“…Study types included case-control study and cohort study. Among them, there were only 10 cohort studies ( 28 , 35 , 39 , 49 , 51 53 , 62 64 ), 11 multicenter studies ( 26 , 30 , 33 , 45 , 46 , 60 64 , 66 ), and 1 study ( 40 ) from the SEER database, and the remaining studies were single-center studies. The median number of cases is 342 (IQR: 200~661), and the median number of cases in training sets is 300 (IQR: 154~533).…”
Section: Resultsmentioning
confidence: 99%